Pengaruh Online Customer Review Terhadap Keputusan Pembelian Secara Online Pada Market Place Shopee - Anasrulloh, Muhammad; W.H., Maria Agatha; Haliza, Hesti Nur (Ecobuss, 2024)
This study aims to quantitatively describe the effect of Online Customer Review on Online Purchasing Decisions through the Shopee Marketplace Guru Pondok Modern Darul Hikmah Tulungagung. The method used in this research is a quantitative descriptive approach method. The population in this study were Pondok Modern Darul Hikmah teachers totalling 240 teachers with a sample size of 72 respondents. The data collection technique in this study used a questionnaire method, the data analysis technique of this study used simple Linear Regression, Hypothesis Test t test and Coefficient of Determination with the help of the SPSS 21.0 for Windows programme. The results of this study indicate that Online Customer Review has a positive and significant effect on Online Purchasing Decisions with a tcount> table value of 2.611> 1.664, The coefficient of determination shows that Online Customer Review is 72.8% while the remaining 27.2% is influenced by other variables.